2011
DOI: 10.1016/j.lwt.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the functional quality of cowpea-fortified traditional African sorghum foods using instrumental and descriptive sensory analysis

Abstract: Despite nutritional advantages, the functional quality of cereal foods tends to decline when fortified with legumes. Traditional African cowpea-fortified sorghum foods were evaluated using instrumental and descriptive sensory analyses. Two sorghum cultivars, NS 5511 (tannin-type) and Orbit (non-tannin-type) were fortified with cowpea (70:30 ratio).Fortification reduced uji (fermented thin porridge) pasting peak viscosity and cool paste viscosity by up to 23% and 12%, respectively, probably as a result of starc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 28 publications
3
37
0
1
Order By: Relevance
“…) and African cowpea‐fortified sorghum food (Anyango et al . ; also, see a review of Lee ). Notably, most lexicons for traditional ethnic foods have been developed using native languages and then translated into English equivalents when necessary for publication; however, also note that several lexicons for traditional ethnic foods were generated using English terms in the U.S.A. (Lee and Chambers ; Chambers et al .…”
Section: Resultsmentioning
confidence: 95%
“…) and African cowpea‐fortified sorghum food (Anyango et al . ; also, see a review of Lee ). Notably, most lexicons for traditional ethnic foods have been developed using native languages and then translated into English equivalents when necessary for publication; however, also note that several lexicons for traditional ethnic foods were generated using English terms in the U.S.A. (Lee and Chambers ; Chambers et al .…”
Section: Resultsmentioning
confidence: 95%
“…Within the toasted fermented cassava products group, white fine gari had the highest BD (57 %), dispersibility (43 %), SWP (635 %) and SI (4 %) values, while yellow kpo-kpo gari had the lowest values for these parameters, but with higher WAC (515 %) levels. The high WAC value shown for yellow kpo-kpo gari implies that its starch structure is more loosely bound together than white fine gari, which has a low WAC [41]. The OAC was higher in yellow fine gari (228 %) but lower in white kpo-kpo gari (224 %) while the LGC value was higher for white kpo-kpo gari (15 %) than for white fine gari (13 %).…”
Section: Pasting Properties Of Dried Cassava Productsmentioning
confidence: 94%
“…Assessment of the potential industrial applications of commercial dried cassava products in Nigeria 601 fiber content levels and compactness in their starch molecular structures, as both are more starchy than fufu and HQCF [22,41]. I n addition, the high OAC values seen for lafun and HQCF are typical for food ingredients that retain flavor in food after having been cooked into a paste.…”
Section: Pasting Properties Of Dried Cassava Productsmentioning
confidence: 99%
“…This could have been due to the high content of coloured finger millet and low content of white maize in this thin porridge. Pigmented grains are rich in phenolic acids which stain porridges with a dark colour during cooking (Anyango et al, 2011;Kebakile, 2008). Comparison of thin porridges made from cereal-based composite flours showed that irrespective of the method of pH adjustment, thin maizesorghum (75:25) porridges were lighter, yellower and redder than the finger millet-maize (90:10) porridges.…”
Section: Objective Evaluation Of the Colour Of Thin Porridgementioning
confidence: 99%